2020
DOI: 10.1111/ahe.12596
|View full text |Cite
|
Sign up to set email alerts
|

Osteomorphological features of the hind limb bones of Saiga antelope (Saiga tatarica)

Abstract: The intralimb indices and calcaneal linear metrics are known as the reliable predictors of locomotor adaptation in artiodactyls. The osteological features of hindlimb in adult Saiga (Saiga tatarica) were described, and its correlation with cursoriality and habitat adaptation was discussed. Gross anatomy data showed Saiga owned the deep acetabulum as a broad lunate surface, the large acetabular anteversion, the well‐developed ischiatic tuberosity and the prominent gluteal lines. It also presented the robust rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Differences among sheep and goats in this anatomical region have not been explored, however researchers have found that the length of the cubonavicular facet is significantly longer in open-adapted bovids than in bovids from forested environments. The cubonavicular facet is also significantly longer in wild cursorial bovids than in semi-free and domestic cursorial bovids, like sheep [ 25 , 26 ]. All these results point to a functional signal in these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences among sheep and goats in this anatomical region have not been explored, however researchers have found that the length of the cubonavicular facet is significantly longer in open-adapted bovids than in bovids from forested environments. The cubonavicular facet is also significantly longer in wild cursorial bovids than in semi-free and domestic cursorial bovids, like sheep [ 25 , 26 ]. All these results point to a functional signal in these differences.…”
Section: Discussionmentioning
confidence: 99%
“…All these results point to a functional signal in these differences. In fact, the morphology of the calcaneum is considered to clearly reflect lifestyle-related functional adaptation in artiodactyls [ 26 ]. Similarly, using GM analysis, sheep astragali have been found to have flatter and elongated plantar surfaces and to be more compressed than those of sheep [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bones were manually oriented and positioned according to the percentage length as described by Skedros et al . [ 13 ] ( Figure-2 ) [ 1 , 7 , 9 , 13 , 14 ]. The diaphyseal length of each bone was measured using a digital Vernier caliper (Mitutoyo, Japan), and the error was controlled to within 1000ths of a millimeter.…”
Section: Methodsmentioning
confidence: 99%
“…Habitual locomotor patterns determined by habitat affect the loads placed on limb bones during locomotion and influence variations in bone morphology [ 1 , 2 ]. Thus, such bone morphology variations are considered to be adaptive responses to loading conditions that directly reflect lifestyle-related functional bone adaptation [ 1 , 3 ]. The calcaneus is the main weight-bearing bone in the hock joint of artiodactyls and presents a habitually loaded cantilevered beam-like structure during bending.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation